Mental health, ethnicity and the UK armed forces: historical lessons for research and policy - Jones, E; Palmer, L; Bhui, K (Elsevier, 2024)
Background: UK armed forces have recruited from other races and ethnicities at times of crisis. To meet diversity targets, they have also recruited indigenous groups of non-White British heritage. Considered at greater risk of mental health problems generally, these populations are likely to suffer more in combat and in transition to civilian life. Yet, there is little data on how they fare.